World trade and the poor countries : implications of WTO rules for LDCs and the role of UNIDO - Assaf, George B. (1998)
Notes that the new world trading system resulting from the conclusion of the Uruguay Round and the WTO agreements or rules together with further liberalization, pose new challenges and opportunities for LDCs. Examines the role UNIDO can play to assist in the development of appropriate industrial capacities.